North American monsters : a contemporary legend casebook - Puglia, David (Utah State University Press, 2022)
"Mining a broad cross-section of diverse folklore journals and books that demonstrates notable legendary monster research and encourages future scholarly monster pursuits. Focusing on ostensibly living creatures strongly tied to specific geographic areas, the volume offers nineteen folkloristic case studies from the last half-century of specific monsters in native habitats"--